TANTANGAN GURU DALAM MENERAPKAN SIKAP PEDULI LINGKUNGAN: STUDI KASUS DI SANGGAR BIMBINGAN AT-TANZIL CHERAS MALAYSIA - Khoirunnisa, Nida; Maya Ratu , Fadilla (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research identifies teacher challenges in implementing environmental care attitudes at Sanggar Bimbingan (SB) At-Tanzil, Cheras, Malaysia. Using a qualitative case study approach, data were gathered through interviews and observations. Findings reveal dual challenges: infrastructure limitations and student heterogeneity. The use of a residential living room as a classroom creates a functional duality that restricts ecological practices to elementary activities like sweeping and using shared domestic waste bins. Furthermore, student grouping based on literacy/numeracy skills rather than age results in diverse cognitive maturity. Older students with higher cognitive abilities show better initiative, while younger students require constant supervision and direct instructions. Following Piaget’s theory, environmental awareness in SB At-Tanzil is closely linked to cognitive development. Success in this informal setting depends on the teacher's pedagogical strategies in bridging developmental gaps and managing limited domestic facilities.